Development of RPS Model Based on Integration of Science and Islam (Prosiding Keislaman dan Sains, 2025)
The purpose of this study is to develop an ideal model of RPS integration of science and Islam at the Islamic University of Riau. This type of research is research and development (R&D) using the ADDIE model with stages including 1) Analysis, 2) Design, 3) Development, 4) Implementation and 5) Evaluation. The results of this study are first, For integration at the Islamic University of Riau has not been fully implemented. This can be seen from the absence of a standard reference for the application of integration even though the concept of integration of Islam and science has existed since the establishment of this campus, the limited competence of Lecturers especially in teaching integration materials, and minimal student insight. In addition, there has been no development of a specific RPS model based on the integration of science and Islam that can be applied at the Islamic University of Riau, especially in the field of education that produces scientific courses on integration as stated in the Semester Learning Plan (RPS). Second, the “RPS Based on ISI (Integration of Science and Islam)” model is considered relevant to the concept of Integration at the Islamic University of Riau because it is based on the results of data analysis conducted based on studies on the integration of science and Islam at several Islamic Universities in Indonesia and literature studies relevant to the integration of Science and Islam in the field
Keywords: Model; RPS; Integration of Islam and Science